Visual procedures for the creation of an ‘expanded script’ throughout confusion and questions in Ignacio Aguero’s films - Panizza Montanari, Tiziana (2018)
This article reflects upon the script of non-fiction cinema. Throughout the documentaries of Chilean filmmaker Ignacio Aguero, there’s an examination of what engines creation in filmmaking: a state of confusion would be fertile for the approach to questions, key to the necesary wandering about in the creative process. Pedro Costa, Andrei Tarkovski, Raul Ruiz y Patricio Guzmán, agree with Aguero that is not possible to construct a film from script writing. In this drift of diagrams, erasures, listings, sketches, an ‘expanded script’ would be a more accurate procedure in the search for a system of relationships established inside of a film.